The Impact of Legal Auditors on Financial Reports Quality in Jordanian Companies - Jarah, Baker Akram Falah; Alzubi, Emran Abdulsalam; Khwaileh, Khaled Mohammad; Ebbini, Mohannad Mohammad; Alqudah, Mamoun. M. A.; Jaradat, Mohammad Suleiman (International Review of Management and Marketing, 2025)
The purpose of this study is to look into the impact of legal auditors (LA) on financial report quality (FRQ) in Jordanian companies. Therefore, the study population is the statutory auditors, and the sample size was 219 to be a representative sample. To select the sample, a simple, purposeful random sample was used to select their emails from the list received from the association above. Furthermore, 326 questionnaires were distributed through the online survey; contact information was obtained through the Jordanian Association of Certified Public Accountants. As a result, 229 responses were received, 92 questionnaires were excluded due to outliers, and thus the study sample included 137 LAs. The hypothesis testing results reveal that all examined constructs’ commitment to professional standards, independence and integrity, LA, legal and accounting knowledge, and responsibility and ethics have significant positive effects on the quality of financial reports. Among these, the LA construct has the most substantial impact, followed by legal and accounting knowledge, highlighting the crucial roles these factors play in ensuring high-quality financial reporting in Jordanian companies. These findings highlight the importance of maintaining high standards of professionalism, understanding, independence, integrity, and moral behavior among LAs to enhance FRQ.